Odd viscosity in chiral active fluids - Debarghya Banerjee (Nature Portfolio, 2017)
Active chiral fluids are a special case of active matter in which energy is introduced into rotational motion via local application of torque. Here Banerjee et al. develop a hydrodynamic theory of such active fluids and connect it with odd viscosity which was previously considered an abstract concept.